X-Ray Florescence Analysis (XRF) of Kaolin in the South Eastern Nigeria (Journal of Basic and Applied Research in Biomedicine, 2022)
The analysis of Kaolin using X-ray Florence analysis was carried out to determine the elements that kaolin are made of , as well as to ascertain Kaolin’s health benefits. There is variation in the concentration of Kaolin in the five South Eastern states of Nigeria. The analysis shows the presence of six (6) major elements (Mg, Ti, Na, K, Fe), six (6) minor elements (V, Mn, Cr, CZn, Rb, Ba) and Seven trace elements (As, Sm, U, Sc, Co, Cs, Th) in the five South Eastern states under studies. The concentrations of most of these elements far exceeds the daily dietary needs or permissible limits of human being and can thus make them toxic unless taken in small doses.